2021
DOI: 10.3390/curroncol28050344
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Surgery: New Issues

Abstract: Since ancient times, breast cancer treatment has crucially relied on surgeons and clinicians making great efforts to find increasingly conservative approaches to cure the tumor. In the Halstedian era (mid-late 19th century), the predominant practice consisted of the radical and disfiguring removal of the breast, much to the detriment of women’s psycho-physical well-being. Thanks to enlightened scientists such as Professor Umberto Veronesi, breast cancer surgery has since impressively progressed and adopted a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…Breast cancer not only harms women's physical bodies, but their mental and psychological health as well, thereby reducing their quality of life (Zamanian et al, 2015). There have been a variety of treatments for the disease, such as surgery and other adjuvant treatments, including radiotherapy and chemotherapy (Magnoni et al, 2021). The prognosis and 5‐year survival rate have improved to some extent (Mkuu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer not only harms women's physical bodies, but their mental and psychological health as well, thereby reducing their quality of life (Zamanian et al, 2015). There have been a variety of treatments for the disease, such as surgery and other adjuvant treatments, including radiotherapy and chemotherapy (Magnoni et al, 2021). The prognosis and 5‐year survival rate have improved to some extent (Mkuu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Risk-reducing surgery is currently witnessing a growing impulse towards the inclusion of breast-conserving therapy (BCT), defined as breast-conserving surgery (BCS) combined with radiotherapy (RT), in the personalized and multidisciplinary approach to managing BC high-risk patients [64]. Indeed, the debate on what the optimal local therapy for women with BRCA-associated BC should be is still ongoing.…”
Section: Not Only Mastectomy: An Opportunity For Breast-conserving Su...mentioning
confidence: 99%
“…Indeed, the choice of treatment for sporadic BC is influenced by factors that include tumor location, breast size, and patient preference [77]. In reference to sporadic BC, multiple prospective randomized trials have found equivalent patient survival rates after BCS and after mastectomy [64]. In particular, Veronesi et al [78] and other authors [79][80][81] found that the 20-year overall survival rate did not differ in a statistically significant way (p = 0.1) between patients who had undergone BCS (58.3%) and those who had undergone mastectomy (58.8%).…”
Section: Not Only Mastectomy: An Opportunity For Breast-conserving Su...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the management of hereditary breast cancer is including BCS as a possible treatment option to offer and discuss in a multidisciplinary fashion with both high and moderate penetrance genes mutated breast cancer patients, if clinically appropriate (Corso and Magnoni, 2021; Yip and Newman, 2021). Recent studies have also reported an association between CDH1 germline mutations and lobular breast cancer: NSM is acquiring an interesting preponderance as a prophylactic tool for breast cancer patients with CDH1 mutation and a significant family history for breast cancer aggregation (Magnoni et al 2021).…”
mentioning
confidence: 99%